The Mechanism of Forming Coagulated Particles in Selective Laser Melting of Cobalt-Chromium-Molybdenum Powder; Key Engineering Materials; Vol. 839 : Materials Science, Mechanical Engineering and Energy: Problems and Prospects for Development, MSMEE 2019 - Saprykin A. A. Aleksandr Aleksandrovich; Sharkeev Yu. P. Yury Petrovich; Saprykina N. A. Natalia Anatolyevna; Ibragimov E. A. Egor Arturovich (2020, 2020)
Title screen